Needs Analysis for Developing a Constraints-Led Traditional Game to Combat Sedentary Lifestyles in Elementary Students - Nawi Nawi; Bambang Priyono (Indonesian Journal of Global Health Research, 2026)
The global epidemic of sedentary lifestyles and excessive gadget use has severely degraded the physical fitness of elementary school students, specifically their agility and cardiovascular endurance. While traditional games like Gobak Sodor offer motor skill benefits, they often lack precise physiological intensity control and utilize passive elimination systems. This study aims to develop and evaluate "Go Ben," a modified Gobak Sodor game designed using the Constraints-Led Approach (CLA) to combat sedentary behaviors. Employing the Borg and Gall Research and Development (R&D) methodology, the study involved Grade 5 students across five elementary schools in the Cirebon region. Participants were selected utilizing a purposive sampling technique, which initially involved a sample of 12 to 15 students for the preliminary field test, before expanding to a main sample of 60 students for operational field testing. The CLA framework was applied to manipulate task, environmental, and individual constraints, replacing passive elimination with active penalties and introducing cognitive tools like "Magic Cards". Following expert validation that scored the model at 95.3% feasibility, a quasi-experimental Pretest-Posttest Control Group Design was conducted on the 60 sampled students. The results demonstrated that the "Go Ben" intervention significantly enhanced agility, with median shuttle run times decreasing from 12.45 to 11.24 seconds (p < 0.001). Additionally, cardiovascular endurance improved significantly, with median Bleep Test scores rising from 18.54 to 20.00 (p < 0.001), successfully outperforming conventional physical education methods (p = 0.045). Ultimately, this CLA-modified game serves as a highly effective, continuous-flow physical training instrument designed to optimize students' physical conditioning, prevent early obesity, and simultaneously preserve local cultural heritage.